More action needed: Psychotropic prescribing in Australian residential aged care. (February 2019) - Westbury, Juanita; Gee, Peter; Ling, Tristan; Kitsos, Alex; Peterson, Gregory
Objective: For at least two decades, concerns have been raised about inappropriate psychotropic prescribing in Australian residential aged care facilities, due to their modest therapeutic benefit and increased risk of falls and mortality. To date, the majority of prevalence data has been collected in Sydney exclusively and it is not known if recent initiatives to promote appropriate psychotropic prescribing have impacted utilisation. Thus, we aimed to comprehensively analyse psychotropic use in a large national sample of residential aged care facility residents. Method: A cross-sectional, retrospective cohort study of residents from 150 residential aged care facilities distributed nationally during April 2014–October 2015. Antipsychotic, anxiolytic/hypnotic and antidepressant utilisation was assessed, along with anticonvulsant and anti-dementia drug use. Negative binomial regression analysis was used to examine variation in psychotropic use. Results: Full psychotropic prescribing data was available from 11, 368 residents. Nearly two-thirds (61%) were taking psychotropic agents regularly, with over 41% prescribed antidepressants, 22% antipsychotics and 22% of residents taking benzodiazepines. Over 30% and 11% were charted for 'prn' (as required) benzodiazepines and antipsychotics, respectively. More than 16% of the residents were taking sedating antidepressants, predominantly mirtazapine. South Australian residents were more likely to be taking benzodiazepines ( p  < 0.05) and residents from New South Wales/Australian Capital Territory less likely to be taking them ( p  < 0.01), after adjustment for rurality and size of residential aged care facility. Residents located in New South Wales/Australian Capital Territory were also significantly less likely to take antidepressants ( p  < 0.01), as were residents from outer regional residential aged care facilities ( p  < 0.01). Antipsychotic use was not associated with State, rurality or residential aged care facility size. Conclusion: Regular antipsychotic use appears to have decreased in residential aged care facilities but benzodiazepine prevalence is higher, particularly in South Australian residential aged care facilities. Sedating antidepressant and 'prn' psychotropic prescribing is widespread. Effective interventions to reduce the continued reliance on psychotropic management, in conjunction with active promotion of non-pharmacological strategies, are urgently required.